Total Protein Requirement of Beef Cattle II: Feeding By-Product Feedstuffs. - Jeffrey N. Carter (EDIS)
AN168, a 4-page fact sheet by Jeffrey N. Carter, discusses the nutritional contributions of by-product feedstuffs and how to compare the economic values of different feedstuffs. Includes a table of protein and energy concentrations of selected feedstuffs. Published by the UF Department of Animal Science, February 2007.